2023
DOI: 10.1101/2023.11.30.569347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transcriptomics of seed nourishing tissues: uncovering conserved and divergent pathways in seed plants

Ana Marcela Florez-Rueda,
Célia M. Miguel,
Duarte D. Figueiredo

Abstract: SummaryThe evolutionary and ecological success of Spermatophytes is intrinsically linked to the seed habit, which provides a protective environment for the pre-development of the new generation. This environment includes an ephemeral nourishing tissue that supports embryo growth. In gymnosperms this tissue originates from the asexual proliferation of the maternal megagametophyte, while in angiosperms it is a product of fertilization, and is called the endosperm. The emergence of these nourishing tissues is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 225 publications
0
0
0
Order By: Relevance
“…It has also been shown that brassinosteroids are involved in signalling between the maternal seed coat and the endosperm ( Lima et al , 2023 , Preprint). These hormonal exchanges seem very conserved in most angiosperms ( Florez-Rueda et al , 2023 , Preprint). Likewise, the central cell-derived ESF1 peptides contribute to proper embryo development ( Costa et al , 2014 ), and even maternal morphogenetic signals are suggested to be involved in embryo patterning in Arabidopsis ( Ray et al , 1996 ).…”
Section: The Maternal Tissue As a Diffusion Barriermentioning
confidence: 99%
“…It has also been shown that brassinosteroids are involved in signalling between the maternal seed coat and the endosperm ( Lima et al , 2023 , Preprint). These hormonal exchanges seem very conserved in most angiosperms ( Florez-Rueda et al , 2023 , Preprint). Likewise, the central cell-derived ESF1 peptides contribute to proper embryo development ( Costa et al , 2014 ), and even maternal morphogenetic signals are suggested to be involved in embryo patterning in Arabidopsis ( Ray et al , 1996 ).…”
Section: The Maternal Tissue As a Diffusion Barriermentioning
confidence: 99%